ASSESSMENT AND ANALYSIS OF ECOLOGICAL ENTREPRENEURSHIP IN THE EUROPEAN UNION COUNTRIES - Urban , O.A.; Chyzh , N.M. (The actual problems of regional economy development, 2025)
The article examines current trends in the development of ecological entrepreneurship in the European Union (EU) countries. An assessment of key indicators characterizing environmentally oriented entrepreneurial activity has been conducted, along with an analysis of the impact of government policies and international environmental standards on the sector’s growth. Special attention is given to mechanisms for supporting ecological businesses, financial incentives, and innovative approaches that contribute to the implementation of sustainable technologies. Based on the experience of EU countries, the article identifies prospects for the development of ecological entrepreneurship in Ukraine and proposes possible measures for its activation. The aim of the study is a comprehensive assessment and analysis of the development of ecological entrepreneurship in the countries of the European Union based on the examination of key indicators of the environmental economy in recent years, identification of main trends and factors influencing the efficiency and dynamics of this sector, as well as the formulation of scientifically grounded recommendations to promote sustainable development and enhance the competitiveness of ecological enterprises in the region. The article reveals the essence of ecological entrepreneurship through the lens of balanced development principles. The primary goal of such entrepreneurship is to create an effective model that harmoniously combines profit generation with environmental preservation. The impact of globalization on ecological entrepreneurship is outlined. While globalization fosters the expansion of economic relations, it also poses significant risks, particularly the increasing divide between developed economic centers and peripheral regions. This further exacerbates disparities in socio-economic, environmental, and scientific-technical development among nations. The current global economic model is geared toward expanding ecological and economic expansion, manifested in forms of ecological separatism and ecological neocolonialism. This intensifies conflicts within the global economic space.